Clinically Important Differences for Mobility Measures Derived from the Testosterone Trials. Issue 2 (18th November 2020) - Stephens‐Shields, Alisa J.; Farrar, John T.; Ellenberg, Susan S.; Storer, Thomas W.; Gill, Thomas M.; Basaria, Shehzad; Pahor, Marco; Cauley, Jane A.; Ensrud, Kristine E.; Preston, Peter; Cella, David; Snyder, Peter J.; et al.
Abstract : BACKGROUND/OBJECTIVES: Accurate estimates of clinically important difference (CID) are required for interpreting the clinical importance of treatments to improve physical function, but CID estimates vary in different disease populations. We determined the CID for two common measures of walking ability in mobility‐limited older men. Design: Longitudinal, multisite placebo‐controlled trial. Setting/Participants: Men enrolled in the Testosterone Trials who had self‐reported mobility limitation and gait speed less than 1.2 m/second (n = 429). Testosterone‐ and placebo‐allocated participants were combined for this study. RESULTS: Mean changes from baseline, adjusting for time‐in‐intervention and site, were 29.6, 13.2, 12.5, −2.4, and −32.6 m for 6MWD, and 15.4, 7.2, 2.1, −3.4, and −7.2 for PF10 in men who reported their mobility was "very/much better, " "little better, " "no change, " "little worse, " or "much worse, " respectively. CID estimates using regression, ROC, and eCDF varied from 5.0–29.6 m for 6MWD, and 5.0–15.2 points for PF10. CONCLUSION: CID estimates vary by the population studied and by the method and precision of measurement. Increases of 16 to 30 m for 6MWD and 5 to 15 points for PF10 over 12 months appear to be clinically meaningful in mobility‐limited, older hypogonadal men. These CID estimates may be useful in the design of efficacy trials of therapies to improve physical function.